Transcriptome Analysis for Identification of Genes Related to Growth and Development, Digestion and Detoxification, Olfaction in the Litchi Stink Bug Tessaratoma papillosa - Cheng, Lin; Han, Shuncai; Jiang, Jingtao; Li, Haichao; Peng, Lingfei (Frontiers in Physiology, 2022)
Tessaratoma papillosa is a major pest of Litchi chinensis and Dimocarpus longan. Adult and nymph secretions are not only harmful to plants but also to humans. At present, there are not a lot of research on T. papillosa, especially omics research. We used high-throughput sequencing technology to sequence the T. papillosa transcriptome and obtained 67,597 unigenes homologous to Halyomorpha halys (88.03%). Subsequently, RNA-SEQ and comparative analyses were performed on the 14 different developmental stages and tissues. A total of 462 unigenes related to growth and development, 1,851 unigenes related to digestion and detoxification, and 70 unigenes related to olfaction were obtained. Moreover, expression analysis showed that the T. papillosa major life activities genes are uniformly expressed across all developmental states. However, the adult midgut gene expression patterns were utterly different from that of the nymphs. Similarly, female fat body genes exhibited distinct expression patterns compared to that of males and nymphs. Thus, different developmental stages and physiological functions affect gene expression patterns. We also found that most of the differential genes were associated with cellular maintenance. This study will help understand the growth and development of litchi stink bugs, their choice of host plants, food digestion and detoxification, and their reproductive behavior. In addition, this result can provide reference information for some target genes in the process of control of T. papillosa.